2021
DOI: 10.1097/jcp.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bedtime Dosing With Suvorexant and Zolpidem on Balance and Psychomotor Performance in Healthy Elderly Participants During the Night and in the Morning

Abstract: Purpose/BackgroundThis study was designed as an early assessment of the safety of the orexin receptor antagonist suvorexant, but also included exploratory assessments of balance and psychomotor performance that are the focus of this report.Methods/ProceduresThis was a double-blind, randomized, 3-period, crossover, phase 1 study. Balance and psychomotor performance were evaluated during the night in 12 healthy elderly participants after bedtime administration of suvorexant 30 mg (a supratherapeutic dose), the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, there was no significant difference in body sway reported for lemborexant (5 or 10 mg) compared with placebo in the morning waketime in healthy adults aged 55 years or older, while zolpidem-ER did show a significant difference (worsening) compared with placebo (Murphy, Kumar, Zammit, Rosenberg, & Moline, 2020 ). It was reported that suvorexant (30 mg) also has no difference in postural stability compared with PBO or zolpidem (5 mg) 8 h after dose (Bland et al, 2021 ). There were no significant differences in efficacy or safety of lemborexant treatments between patients with and without comorbidities, i.e., history of depression, anxiety, gastro-esophageal reflux disease, migraine, hypertension, diabetes, and renal dysfunction [Nierenberg et al, 2020 ; ‘Pharmaceuticals and Medical Devices Agency (PMDA) Shinsa Houkokusho (Review Report),’, 2020 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference in body sway reported for lemborexant (5 or 10 mg) compared with placebo in the morning waketime in healthy adults aged 55 years or older, while zolpidem-ER did show a significant difference (worsening) compared with placebo (Murphy, Kumar, Zammit, Rosenberg, & Moline, 2020 ). It was reported that suvorexant (30 mg) also has no difference in postural stability compared with PBO or zolpidem (5 mg) 8 h after dose (Bland et al, 2021 ). There were no significant differences in efficacy or safety of lemborexant treatments between patients with and without comorbidities, i.e., history of depression, anxiety, gastro-esophageal reflux disease, migraine, hypertension, diabetes, and renal dysfunction [Nierenberg et al, 2020 ; ‘Pharmaceuticals and Medical Devices Agency (PMDA) Shinsa Houkokusho (Review Report),’, 2020 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary phase, a total of 2,085 articles were searched, and after careful screening, 27 RCTs and 2 case-control studies were eventually considered eligible for analysis ( Figure 1 ) (Ancoli-lsrael, 2010 ; McCall et al, 2010 ; Menza et al, 2010 ; Mets et al, 2011 ; Bettica et al, 2012 ; Herring et al, 2012 , 2013 , 2014 , 2016 , 2017 , 2020 ; Hoever et al, 2012 , 2013 ; Uchimura et al, 2012a , b ; Sun et al, 2013 ; Leufkens et al, 2014 ; Tek et al, 2014 ; Vermeeren et al, 2014 , 2016 , 2019 ; Spierings et al, 2015 ; Connor et al, 2016 ; Dauvilliers et al, 2020 ; Dopheide, 2020 ; Karppa et al, 2020 ; Murphy et al, 2020 ; Zammit et al, 2020 ; Bland et al, 2021 ; Boof et al, 2021 ; Louzada et al, 2022 ). The subjects of these studies were from America, Australia, Britain, and Germany, among others.…”
Section: Resultsmentioning
confidence: 99%
“…Suvorexant, the first available dual orexin receptor antagonist, can be dosed at 5 mg, 10 mg, and 20 mg, although clinical trials initially focused on higher doses of up to 40 mg (30 mg in people ≥65 years old) for an efficacy range 51 . Trials have shown similar alertness thresholds 52 and reaction times 53 during middle-of-the-night awakenings in patients taking suvorexant versus placebo, in contrast to the sedation noted with benzodiazepines and nonbenzodiazepine GABA receptor agonists. Lemborexant has demonstrated improved sleep latency and wake-after-sleep onset 54 .…”
Section: Clinical Management Of Insomniamentioning
confidence: 99%